GAMBARAN POLA MAKAN, TINGKAT STRES, DAN KELUHAN GEJALA GASTRITIS (MAAG) PADA SALES PROMOTION GIRL (SPG) DI MATAHARI DEPARTEMEN STORE PLAZA MEDAN FAIR - Risky Malinda; Etti Sudaryati; Jumirah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
The emergence complaints of gastritis symptoms caused by many factors, among others is improper diet and stress levels of individual. Purpose of this research is described about eating pattern, stress levels, and complaints of gastritis symptoms on Sales Promotion Girls (SPG) in Matahari Department Store Plaza Medan Fair.   Design of research using cross-sectional with 81 samples. Samples were determined by simple random sampling technique. The primary data such as diet pattern, complaints of gastritis symptoms, and stress level from each SPG were collected by direct interview method with structural questionnaire guidance. Method of data analysis used descriptive analysis supported by computerized frequency.   The results showed that 86.4 % of SPG have complaints about gastritis symptoms. Most of them have good eating pattern but 82.8% of them have complaints about gastritis symptoms. Almost of SPG have bad eating schedule and 87.5% of them experienced with gastritis symptoms. Types of foods that consumed by SPG were risky foods that caused complaints gastritis symptoms such as fried foods, spicy, containing coconut milk and gassy. SPG with less energy intake, 83,9% of them have complaints about gastritis symptoms and SPG with less carbohydrate intake, 86,1% of them have complaints about gastritis symptoms too. Most of SPG have more protein and good fat intake. However, 86.5% SPG with more protein intake and 90.6% SPG with good fat intake also have complaints of gastritis symptoms. SPG only suffers stress level between mild and medium level. SPG with medium stress levels were 97.4% and suffers complaint of gastritis symptoms.   SPG should try to manage their eating pattern properly while applying a good meal habit for each day, avoiding foods which can triggered gastritis symptoms, fulfil their nutrients needs, and manage their stress level well.   Keywords : diet, stress level, complaints of gastritis symptoms, SPG